Lomi And Totò : An Ethiopian-Italian Colonial or Postcolonial “Love Story”? - Giovanna Trento (Conserveries Mémorielles)
Lomi and Totò. An Ethiopian-Italian Colonial or Postcolonial “Love Story”? introduces various and still open questions related to the current necessity of a deeper study of the Italian colonial presence in the African Horn. The source of this article is the relationship between Lomi and Totò, an Ethiopian woman and an Italian man who are not alive anymore, as it is seen and told by their five children (with some additional illuminating interviews). This story started during the Italian colonial fascist period, continued in the Fifties and Sixties in postcolonial East Africa, ended up in Italy in the Eighties, and is still alive in the memory of Lomi and Totò descendents. This “love story” has different shades and can be read from several points of view: personal, sentimental, familiar, social, anthropological, and historical. For some aspects it is unique, but for others it is exemplary of its time and allows us to look into important dynamics during wide and complex periods. Giovanna Trento in this article, thanks to the observation of this “private history”, highlights a certain controversial and unstable degree of fluidity between colonial and postcolonial periods, also questioning the degree of freedom individuals might have within a given social framework, thus suggesting some crucial and sometimes ambiguous issues related to: the use of racial laws in the fascist period; notions of concubinage, marriage and citizenship; gender and power relations; subaltern conditions and marginality within Italian colonialism; discrepancies between portraying African women and relating to them; new African-Italian identities; building collective memory and family storytelling; reproducing, suffering, or overcoming the “colony” today.